Is China’s capitalism sustainable? - Karnia, Krystian (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
During the last three decades China’s economic system has undergone a great transformation from communism to some form of state-led capitalism, in which ‘the state’ means actually ‘the Communist Party’. Looking at the average rates of growth and reduction in poverty indices, the Party’s evolutionary approach to reforms brought a successful catch-up process. However, the picture of the reforms is much more complex with the officials acting both as a developmental and inequality-enhancing force. The paper takes a closer look at the role of the state (and political actors) in economic development from socio-economical and macroeconomic perspective. It is argued that China’s system is hardly Nash-like equilibrium and correction in the growth distribution pattern is required (in fact, there have already been first signs of rebalancing).